Conductive polymer dispersion and method for producing the same, and capacitor and method for producing the same

A low-viscosity conductive polymer dispersion, comprising π-conjugated polymers and polyanions with alkylphosphonic acids, addresses the invasion issue in capacitor manufacturing, resulting in capacitors with reduced ESR and enhanced performance.

JP2025011517APending Publication Date: 2025-01-24SHIN ETSU POLYMER CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023113686
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-11
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The challenge in manufacturing capacitors lies in the difficulty of the conductive polymer dispersion invading the porous dielectric layer or the narrow gap between the anode and cathode due to high viscosity, which affects the formation of a solid electrolyte layer.

Method used

A low-viscosity conductive polymer dispersion is developed using a water-based medium with a high water content, containing π-conjugated conductive polymers like poly(3,4-ethylenedioxythiophene) and polyanions such as polystyrene sulfonic acid, along with alkylphosphonic acids, to form a conductive complex that can penetrate and form a solid electrolyte layer effectively.

Benefits of technology

The low-viscosity dispersion facilitates the formation of a solid electrolyte layer, reducing equivalent series resistance (ESR) and enabling the production of capacitors with improved performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025011517000001_ABST
    Figure 2025011517000001_ABST
Patent Text Reader

Abstract

To provide a low-viscosity conductive polymer dispersion suitable for the production of a capacitor and a method for producing the same, and a capacitor and a method for producing the same.SOLUTION: The present invention provides a method for producing a capacitor 10, using a conductive polymer dispersion containing a π-conjugated conductive polymer, a C4-12 alkylphosphonic acid, a polyanion, and an aqueous dispersion medium. For example, the conductive polymer dispersion is applied to the surface of a dielectric layer 12, formed on the surface of a porous valve-metal anode 11, and then dried to form a solid electrolyte layer 14.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a conductive polymer dispersion containing a π-conjugated conductive polymer and a method for producing the same, as well as a capacitor and a method for producing the same. [Background technology]

[0002] A π-conjugated conductive polymer, whose main chain is composed of a π-conjugated system, forms a conductive complex by doping with a polyanion having an anionic group, and becomes dispersible in water. A capacitor having a solid electrolyte layer formed using a conductive polymer dispersion liquid (conductive polymer-containing liquid) in which such a conductive complex is dispersed is known (for example, Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2020-100744 A Summary of the Invention [Problem to be solved by the invention]

[0004] The solid electrolyte layer of the capacitor in Patent Document 1 and the like is formed by applying a conductive polymer dispersion onto a dielectric layer formed on the surface of an anode by chemical conversion treatment, and then drying and solidifying the coating. The conductive polymer dispersion to be applied is required to be able to penetrate into the porous dielectric layer and into the narrow gap between the anode and cathode, and therefore it is preferable that the viscosity of the conductive polymer dispersion used in the production of the capacitor is low.

[0005] The present invention provides a low-viscosity conductive polymer dispersion suitable for producing a capacitor and a method for producing the same, as well as a capacitor and a method for producing the same. [Means for solving the problem]

[0006] [1] A conductive polymer dispersion comprising a π-conjugated conductive polymer, an alkylphosphonic acid having 4 to 12 carbon atoms, a polyanion, and an aqueous dispersion medium. [2] The conductive polymer dispersion according to [1], wherein the content of water relative to the total mass of the aqueous dispersion medium is 70 mass % or more. [3] The conductive polymer dispersion according to [1] or [2], wherein the π-conjugated conductive polymer is poly(3,4-ethylenedioxythiophene), or the polyanion is polystyrenesulfonic acid, or the π-conjugated conductive polymer is poly(3,4-ethylenedioxythiophene) and the polyanion is polystyrenesulfonic acid. [4] A method for producing a conductive polymer dispersion, comprising a polymerization step of polymerizing a monomer that forms a π-conjugated conductive polymer in a reaction liquid containing a polyanion, an alkylphosphonic acid having 4 to 12 carbon atoms, and an aqueous dispersion medium, to form the π-conjugated conductive polymer and a conductive complex containing the polyanion and the alkylphosphonic acid having 4 to 12 carbon atoms. [5] A capacitor comprising: an anode made of a porous body of a valve metal; a dielectric layer made of an oxide of the valve metal; a cathode made of a conductive material provided on the dielectric layer opposite the anode; and a solid electrolyte layer formed between the dielectric layer and the cathode, wherein the solid electrolyte layer contains a conductive complex including a π-conjugated conductive polymer, a polyanion, and an alkylphosphonic acid having 4 to 12 carbon atoms. [6] The capacitor according to [5], wherein the solid electrolyte layer further contains a basic compound. [7] The capacitor according to [5] or [6], wherein the basic compound is a nitrogen-containing aromatic compound. [8] The capacitor according to any one of [5] to [7], wherein the solid electrolyte layer further contains a polyol compound containing two or more hydroxyl groups. [9] The capacitor according to [8], wherein the polyol compound is diethylene glycol.

[10] A method for producing a capacitor, comprising the steps of applying a conductive polymer dispersion to a surface of a dielectric layer formed on the surface of an anode made of a porous valve metal, and drying the applied conductive polymer dispersion to form a solid electrolyte layer, wherein the conductive polymer dispersion contains a conductive complex containing a π-conjugated conductive polymer and a polyanion, and an alkylphosphonic acid having 4 to 12 carbon atoms, and an aqueous dispersion medium for dispersing the conductive complex. Effect of the Invention

[0007] Since the conductive polymer dispersion of the present invention has a low viscosity, it can be easily impregnated into an object to be coated, and is therefore suitable for producing a capacitor. According to the method for producing a conductive polymer dispersion of the present invention, a conductive polymer dispersion with low viscosity can be prepared. The capacitor of the present invention has a reduced equivalent series resistance (ESR) and excellent performance. According to the method for producing a capacitor of the present invention, the above-mentioned excellent capacitor can be easily produced.

[0008] This invention is believed to contribute to SDGs Goal 12, "Responsible Consumption and Production."

[0009] In this specification and claims, the lower limit and upper limit of a numerical range indicated with "to" are included in the numerical range. [Brief description of the drawings]

[0010] [Figure 1] 1 is a cross-sectional view showing an embodiment of a capacitor of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] ≪Conductive polymer dispersion liquid≫ A first aspect of the present invention is a conductive polymer dispersion liquid containing a π-conjugated conductive polymer, an alkylphosphonic acid having 4 to 12 carbon atoms, a polyanion, and an aqueous dispersion medium. In the conductive polymer dispersion of this embodiment, the π-conjugated conductive polymer and the polyanion preferably form a conductive complex. The conductive complex preferably contains not only the π-conjugated conductive polymer and the polyanion, but also an alkylphosphonic acid having 4 to 12 carbon atoms.

[0012] <Conductive composite> The conductive complex of this embodiment includes a π-conjugated conductive polymer and a polyanion. The polyanion in the conductive complex is doped into the π-conjugated conductive polymer to form a conductive complex having electrical conductivity. In the polyanion, only a part of the anionic groups is doped into the π-conjugated conductive polymer, and the polyanion has excess anionic groups that are not involved in the doping. Since the excess anionic groups are hydrophilic groups, the conductive complex has water dispersibility.

[0013] The conductive complex of this embodiment preferably contains an alkylphosphonic acid having 4 to 12 carbon atoms. The sulfonic acid group of the alkylphosphonic acid having 4 to 12 carbon atoms can be doped into the π-conjugated conductive polymer in the same manner as the anion group of the polyanion. It is presumed that the presence of the alkylphosphonic acid having 4 to 12 carbon atoms in the conductive complex activates molecular motion in the dispersion of the conductive complex, thereby lowering the viscosity of the dispersion.

[0014] (π-conjugated conductive polymer) The π-conjugated conductive polymer may be an organic polymer whose main chain is composed of a π-conjugated system, and examples thereof include polypyrrole-based conductive polymers, polythiophene-based conductive polymers, polyacetylene-based conductive polymers, polyphenylene-based conductive polymers, polyphenylenevinylene-based conductive polymers, polyaniline-based conductive polymers, polyacene-based conductive polymers, polythiophenevinylene-based conductive polymers, and copolymers thereof. From the viewpoint of stability in air, polypyrrole-based conductive polymers, polythiophenes, and polyaniline-based conductive polymers are preferred, and from the viewpoint of transparency, polythiophene-based conductive polymers are more preferred.

[0015] Polythiophene-based conductive polymers include polythiophene, poly(3-methylthiophene), poly(3-ethylthiophene), poly(3-propylthiophene), poly(3-butylthiophene), poly(3-hexylthiophene), poly(3-heptylthiophene), poly(3-octylthiophene), poly(3-decylthiophene), poly(3-dodecylthiophene), poly(3-octadecylthiophene), poly(3-bromothiophene), poly(3-chlorothiophene), and poly(3-iodothiophene). thiophene), poly(3-cyanothiophene), poly(3-phenylthiophene), poly(3,4-dimethylthiophene), poly(3,4-dibutylthiophene), poly(3-hydroxythiophene), poly(3-methoxythiophene), poly(3-ethoxythiophene), poly(3-butoxythiophene), poly(3-hexyloxythiophene), poly(3-heptyloxythiophene), poly(3-octyloxythiophene), poly(3-decyloxythiophene), poly(3-dodecyloxythiophene), oxythiophene), poly(3-octadecyloxythiophene), poly(3,4-dihydroxythiophene), poly(3,4-dimethoxythiophene), poly(3,4-diethoxythiophene), poly(3,4-dipropoxythiophene), poly(3,4-dibutoxythiophene), poly(3,4-dihexyloxythiophene), poly(3,4-diheptyloxythiophene), poly(3,4-dioctyloxythiophene), poly(3,4-didecyloxythiophene), poly(3,4-di dodecyloxythiophene), poly(3,4-ethylenedioxythiophene), poly(3,4-propylenedioxythiophene), poly(3,4-butylenedioxythiophene), poly(3-methyl-4-methoxythiophene), poly(3-methyl-4-ethoxythiophene), poly(3-carboxythiophene), poly(3-methyl-4-carboxythiophene), poly(3-methyl-4-carboxyethylthiophene), and poly(3-methyl-4-carboxybutylthiophene). Examples of polypyrrole-based conductive polymers include polypyrrole, poly(N-methylpyrrole), poly(3-methylpyrrole), poly(3-ethylpyrrole), poly(3-n-propylpyrrole), poly(3-butylpyrrole), poly(3-octylpyrrole), poly(3-decylpyrrole), poly(3-dodecylpyrrole), poly(3,4-dimethylpyrrole), poly(3,4-dibutylpyrrole), poly(3-carboxypyrrole), poly(3-methyl-4-carboxypyrrole), poly(3-methyl-4-carboxyethylpyrrole), poly(3-methyl-4-carboxybutylpyrrole), poly(3-hydroxypyrrole), poly(3-methoxypyrrole), poly(3-ethoxypyrrole), poly(3-butoxypyrrole), poly(3-hexyloxypyrrole), and poly(3-methyl-4-hexyloxypyrrole). Examples of polyaniline-based conductive polymers include polyaniline, poly(2-methylaniline), poly(3-isobutylaniline), poly(2-anilinesulfonic acid), and poly(3-anilinesulfonic acid). Among these π-conjugated conductive polymers, poly(3,4-ethylenedioxythiophene) is particularly preferable because of its excellent conductivity, transparency, and heat resistance. The conductive composite may contain one type of π-conjugated conductive polymer, or two or more types of polymers.

[0016] (Polyanion) A polyanion is a polymer having two or more monomer units each having an anionic group in the molecule. The anionic group of the polyanion functions as a dopant for a π-conjugated conductive polymer, improving the conductivity of the π-conjugated conductive polymer. The anion group of the polyanion is preferably a sulfo group or a carboxy group. Specific examples of such polyanions include polymers having a sulfo group, such as polystyrene sulfonic acid, polyvinyl sulfonic acid, polyallyl sulfonic acid, polyacrylic acid esters having a sulfo group, polymethacrylic acid esters having a sulfo group (for example, poly(4-sulfobutyl methacrylate, polysulfoethyl methacrylate, polymethacryloyloxybenzenesulfonic acid), poly(2-acrylamido-2-methylpropanesulfonic acid), and polyisoprene sulfonic acid; and polymers having a carboxy group, such as polyvinyl carboxylic acid, polystyrene carboxylic acid, polyallyl carboxylic acid, polyacrylic acid, polymethacrylic acid, poly(2-acrylamido-2-methylpropanecarboxylic acid), and polyisoprene carboxylic acid. The polyanion may be a homopolymer in which a single monomer is polymerized, or a copolymer in which two or more monomers are polymerized. Among these polyanions, polymers having a sulfo group are preferred, and polystyrene sulfonic acid is more preferred, since they can provide higher electrical conductivity.

[0017] The weight average molecular weight Mw of the polyanion is not particularly limited and is, for example, preferably from 10,000 to 1,000,000, more preferably from 50,000 to 800,000, further preferably from 100,000 to 600,000, and most preferably from 200,000 to 500,000. When the weight average molecular weight Mw of the polyanion is within the above range, the viscosity of the conductive polymer dispersion of this embodiment becomes appropriately low, and a capacitor with a sufficiently low ESR can be easily produced. The weight average molecular weight Mw of the polyanion is measured by gel filtration chromatography and is the average molecular weight based on mass calculated in terms of pullulan.

[0018] The content ratio of the polyanion contained in the conductive polymer dispersion of this embodiment is, for example, preferably in the range of 1 part by mass to 1000 parts by mass, more preferably 10 parts by mass to 700 parts by mass, and even more preferably 100 parts by mass to 500 parts by mass, relative to 100 parts by mass of the π-conjugated conductive polymer. If the content ratio of the polyanion is equal to or higher than the lower limit, the doping effect on the π-conjugated conductive polymer tends to be stronger, and the conductivity becomes higher. On the other hand, if the content of the polyanion is equal to or lower than the upper limit, the π-conjugated conductive polymer can be sufficiently contained, so that sufficient conductivity can be ensured.

[0019] (Alkylphosphonic acid) The alkylphosphonic acid having 4 to 12 carbon atoms (hereinafter sometimes abbreviated as AP) of this embodiment is a compound having a linear or branched alkane having 4 to 12 carbon atoms as a skeleton, in which at least one hydrogen atom bonded to the alkane is substituted with sulfonic acid. The alkylphosphonic acid is a compound other than the polyanions.

[0020] AP can be bonded to the π-conjugated conductive polymer as a dopant, similar to polyanions. When it functions as a dopant, it is considered that the phosphonic acid group is doped as an anion group. Doping with AP reduces the viscosity of the conductive polymer dispersion, which is preferable for reducing the ESR of the solid electrolyte layer of the capacitor described later, but it may be simply included in the conductive polymer dispersion as an additive without being doped.

[0021] The alkane skeleton is preferably linear. The linear structure facilitates doping of the π-conjugated conductive polymer, resulting in a further reduction in the ESR of the capacitor. The position at which the phosphonic acid group is bonded to the alkane skeleton is preferably the terminal of the alkane, from the viewpoint of facilitating doping. The number of carbon atoms in the alkane skeleton is preferably as large as possible within the range of 4 to 12, from the viewpoint of reducing viscosity and ESR, as shown in the examples described below. Specific examples of preferred APs include n-butylphosphonic acid, n-hexylphosphonic acid, n-octylphosphonic acid, n-decylphosphonic acid, and n-dodecylphosphonic acid.

[0022] The conductive polymer dispersion of this embodiment may contain one type of AP or two or more types of AP. The total content ratio is, for example, preferably from 100 to 5000 parts by mass, more preferably from 300 to 3000 parts by mass, and even more preferably from 500 to 1000 parts by mass, relative to 100 parts by mass of the π-conjugated conductive polymer. If the content is equal to or greater than the lower limit of the above range, the interaction with the π-conjugated conductive polymer tends to be stronger, the viscosity of the conductive polymer dispersion is lowered, and the ESR of the capacitor is further reduced. If the content is equal to or less than the upper limit of the above range, the relative content of the π-conjugated conductive polymer is increased, and sufficient conductivity can be ensured.

[0023] The mass-based content ratio of the polyanion content G1 to the AP content G2 contained in the conductive polymer dispersion of this embodiment, expressed as G1 / G2, is preferably 0.1 to 3.0, more preferably 0.1 to 0.7, even more preferably 0.1 to 0.6, particularly preferably 0.1 to 0.5, and most preferably 0.1 to 0.4. In the most preferred range, it may be any of 0.1 to 0.3, 0.1 to 0.2, 0.2 to 0.4, and 0.3 to 0.4. When the content is within the above range, the viscosity of the conductive polymer dispersion is reduced, and the ESR can be reduced while maintaining the capacitance of the capacitor.

[0024] The mass-based content ratio, expressed as G3 / G2, of the π-conjugated conductive polymer content G3 and the AP content G2 contained in the conductive polymer dispersion of this embodiment is preferably 0.1 to 1.0, more preferably 0.1 to 0.7, even more preferably 0.1 to 0.6, particularly preferably 0.1 to 0.5, and most preferably 0.1 to 0.4. In the most preferred range, it is preferably 0.1 to 0.4, more preferably 0.1 to 0.3, and even more preferably 0.1 to 0.2. When the content is within the above range, the viscosity of the conductive polymer dispersion is reduced, and the ESR can be reduced while maintaining the capacitance of the capacitor.

[0025] The total content of the π-conjugated conductive polymer and polyanion relative to the total mass of the conductive polymer dispersion of this embodiment is preferably 0.1 mass % or more and 5.0 mass % or less, and more preferably 0.5 mass % or more and 2.5 mass % or less. When the content is within the above suitable range, the ESR of a capacitor having a solid electrolyte layer formed from the conductive polymer dispersion can be further reduced.

[0026] The AP content relative to the total mass of the conductive polymer dispersion of this embodiment is preferably from 0.1 to 10 mass%, more preferably from 0.5 to 5.0 mass%, and even more preferably from 1.0 to 3.0 mass%. When the content is within the above suitable range, the ESR of a capacitor having a solid electrolyte layer formed from the conductive polymer dispersion can be further reduced.

[0027] (dispersion medium) The dispersion medium contained in the conductive polymer dispersion is preferably an aqueous dispersion medium containing water because the conductive complex is hydrophilic. Also, a dispersion medium other than water may be contained. The dispersion medium other than water is not particularly limited as long as it does not significantly impair the dispersibility of the conductive complex. Since the conductive complex has excess anion groups derived from polyanions and has high dispersibility in water, the dispersion medium other than water is preferably a water-soluble organic solvent. Here, the water-soluble organic solvent is an organic solvent that dissolves in an amount of 1 g or more in 100 g of water at 20°C, and examples of the water-soluble organic solvent include alcohol-based solvents, ketone-based solvents, and ester-based solvents. The water-soluble organic solvent contained as the dispersion medium may be one type or two or more types.

[0028] The content of water relative to the total mass of the dispersion medium excluding the solid content (non-volatile components) of the conductive polymer dispersion is preferably 70 mass% or more, more preferably 80 mass% or more, even more preferably 90 mass% or more, and may be 100 mass%. When water is contained in an amount equal to or more than the above lower limit, the dispersibility of the conductive complex contained in the conductive polymer dispersion is increased, and the ESR of a capacitor having a solid electrolyte layer formed from the conductive polymer dispersion can be further reduced.

[0029] (Basic compounds) The conductive polymer dispersion may contain one or more basic compounds. The basic compound functions as a Bronsted base that receives protons from the excess anion groups of the polyanion. In order to fulfill this function, the amount of the basic compound dissolved in water is preferably 0.001 g or more per 100 g of water at 20° C. The upper limit of the amount dissolved is not particularly limited, but even if it is about 0.1 g, for example, the above function can be fulfilled sufficiently.

[0030] Examples of the basic compound that can be used include organic or inorganic basic compounds containing nitrogen, hydroxides of alkali metals or Group 2 metals, various carbonates and hydrogen carbonates, etc. Examples include hydroxides of alkali metals, quaternary ammonium hydroxides or salts thereof, ammonia, amines, etc. Specific examples of the alkali metal hydroxide include potassium hydroxide and sodium hydroxide. Specific examples of carbonates or hydrogen carbonates include ammonium hydrogen carbonate, ammonium carbonate, potassium hydrogen carbonate, potassium carbonate, sodium hydrogen carbonate, and sodium carbonate. Specific examples of the quaternary ammonium hydroxide or a salt thereof include tetramethylammonium hydroxide, tetraethylammonium hydroxide, and tetrabutylammonium hydroxide.

[0031] Examples of the amine include aliphatic tertiary amines and nitrogen-containing aromatic compounds. Examples of the aliphatic tertiary amine include triethanolamine, trimethylamine, triethylamine, tripropylamine, tributylamine, trihexylamine, trioctylamine, triphenylamine, tribenzylamine, and trinaphthylamine.

[0032] Examples of nitrogen-containing aromatic compounds (aromatic compounds in which at least one nitrogen atom forms a ring structure) include pyrrole, indole, imidazole, 2-methylimidazole, 2-propylimidazole, N-methylimidazole, N-propylimidazole, N-butylimidazole, 1-(2-hydroxyethyl)imidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 1-benzyl-2-methylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, and 1-cyanoethyl-2-ethyl-4-methylimidazole. Examples of the aryloxy group include 2-phenyl-4,5-dihydroxymethylimidazole, 1-acetylimidazole, 2-aminobenzimidazole, 2-amino-1-methylbenzimidazole, 2-hydroxybenzimidazole, 2-(2-pyridyl)benzimidazole, pyridine, pyrimidine, pyrazine, and derivatives thereof such as alkyl-substituted products (e.g., substituted with an alkyl group having 1 to 4 carbon atoms, such as methyl, ethyl, propyl, or butyl), halogen-substituted products (e.g., substituted with a halogen group, such as fluoro, chloro, or bromine), and nitrile-substituted products. Of these, nitrogen-containing aromatic compounds are preferred, and imidazole is more preferred.

[0033] The content of the basic compound in the conductive polymer dispersion is, for example, preferably 1 part by mass or more and 1000 parts by mass or less, more preferably 5 parts by mass or more and 100 parts by mass or less, and even more preferably 10 parts by mass or more and 50 parts by mass or less, relative to 100 parts by mass in total of the π-conjugated conductive polymer and the polyanion. When the content is in the above preferred range, the ESR of the capacitor can be further reduced.

[0034] The content of the basic compound contained in the conductive polymer dispersion is preferably such that the pH of the conductive polymer dispersion (25°C) is 2.0 to 8.0, more preferably 2.0 to 5.0, and even more preferably 2.0 to 3.0. Within the above preferred range, the ESR of the capacitor can be further reduced.

[0035] (Polyol Compound) The conductive polymer dispersion may contain one or more polyol compounds. Here, the polyol compound refers to a compound having two or more hydroxyl groups, which is different from the π-conjugated conductive polymer, the polyanion, and the basic compound. By containing the polyol compound, the ESR of the capacitor can be further reduced.

[0036] Examples of the polyol compound include one or more selected from ethylene glycol, diethylene glycol, propylene glycol, 1,4-butanediol, glycerin, pentaerythritol, trimethylolpropane, and trimethylolethane.

[0037] The content of the polyol compound contained in the conductive polymer dispersion is, for example, preferably 100 parts by mass or more and 10,000 parts by mass or less, more preferably 200 parts by mass or more and 2,000 parts by mass or less, and even more preferably 300 parts by mass or more and 1,000 parts by mass or less, relative to 100 parts by mass in total of the π-conjugated conductive polymer and the polyanion. Within the above preferred range, the ESR of the capacitor can be further reduced.

[0038] The content of the polyol compound relative to the total mass of the conductive polymer dispersion is preferably from 1 to 15% by mass, more preferably from 3 to 12% by mass, and even more preferably from 5 to 9% by mass. When it is in the above preferred range, the coatability of the conductive polymer dispersion is improved, and the ESR of the capacitor can be further reduced.

[0039] (Optional Additives) The conductive polymer dispersion may contain any additive other than the conductive complex within the scope of the present invention, and the content ratio is appropriately determined depending on the type of additive, but can be, for example, 1 to 1000 parts by mass per 100 parts by mass of the total of the π-conjugated conductive polymer and the polyanion. Here, the optional additive is a compound other than the basic compound, the polyol compound, and the dispersion medium.

[0040] Examples of the optional additives include a surfactant, an inorganic conductive agent, an antifoaming agent, a coupling agent, an antioxidant, and an ultraviolet absorbing agent. The surfactant may be a nonionic, anionic or cationic surfactant, with the nonionic surfactant being preferred from the standpoint of storage stability. Polymer surfactants such as polyvinyl alcohol and polyvinylpyrrolidone may also be added. Examples of the inorganic conductive agent include metal ions, conductive carbon, etc. Metal ions can be generated by dissolving a metal salt in water. The antifoaming agent includes silicone resin, polydimethylsiloxane, silicone oil, and the like. The coupling agent may be a silane coupling agent having a vinyl group, an amino group, an epoxy group, or the like. Examples of the antioxidant include phenol-based antioxidants, amine-based antioxidants, phosphorus-based antioxidants, sulfur-based antioxidants, and sugars. Examples of the ultraviolet absorber include benzotriazole-based ultraviolet absorbers, benzophenone-based ultraviolet absorbers, salicylate-based ultraviolet absorbers, cyanoacrylate-based ultraviolet absorbers, oxanilide-based ultraviolet absorbers, hindered amine-based ultraviolet absorbers, and benzoate-based ultraviolet absorbers.

[0041] The viscosity of the conductive polymer dispersion of this embodiment at 25° C. is preferably from 1 cP to 50 cP, more preferably from 1 cP to 40 cP, even more preferably from 1 cP to 30 cP, and most preferably from 1 cP to 20 cP. When the thickness is equal to or greater than the lower limit of the above range, the thickness of the coating applied onto the dielectric layer can be ensured, making it easy to form a solid electrolyte layer of appropriate thickness. When the content is equal to or less than the upper limit of the above range, it becomes easy to cause the conductive polymer dispersion to penetrate into the fine porous structure preliminarily formed on the surface of the dielectric layer, and to form a solid electrolyte layer also inside the structure. The viscosity was measured at 25° C. using a tuning fork vibration viscometer in accordance with JIS Z8803:2011 (viscosity measurement method using a vibration viscometer).

[0042] <Method for producing conductive polymer dispersion> A second aspect of the present invention is a method for producing a conductive polymer dispersion, comprising a polymerization step of forming a conductive complex containing a π-conjugated conductive polymer and the polyanion by polymerizing a monomer that forms a π-conjugated conductive polymer in a reaction liquid containing a polyanion, an alkylphosphonic acid (AP) having 4 to 12 carbon atoms, and an aqueous dispersion medium. The conductive polymer dispersion of the first embodiment can be produced by the production method of this embodiment.

[0043] A reaction solution containing the monomer, the polyanion, AP, and water is prepared, and the monomer is polymerized to form a π-conjugated conductive polymer. In the reaction solution, the polyanion is naturally doped into the π-conjugated conductive polymer, and a conductive complex consisting of the π-conjugated conductive polymer and the polyanion is formed. At this time, the phosphonic acid group of the AP can be doped into the π-conjugated conductive polymer in the same manner as the anion group of the polyanion. It is presumed that the presence of AP in the conductive complex in this way activates molecular motion in the dispersion of the conductive complex, thereby lowering the viscosity of the dispersion. From the above, the conductive complex obtained by the manufacturing method of this embodiment contains AP.

[0044] The synthesis of the conductive complex in the reaction solution can be carried out in the same manner as in conventional synthesis of a conductive complex, except that AP is added to the reaction solution.

[0045] Since the aqueous dispersion medium contained in the reaction liquid contains water, the polymerization reaction of the monomers proceeds stably, and the resulting conductive composite is obtained in a state where it is stably dispersed in the aqueous dispersion medium. The aqueous dispersion medium may contain a dispersion medium other than water. The dispersion medium other than water may be any one that does not inhibit polymerization, and is preferably a water-soluble organic solvent. Here, the water-soluble organic solvent is an organic solvent that dissolves in 100 g of water at 20°C in an amount of 1 g or more, and examples of the water-soluble organic solvent include alcohol-based solvents, ketone-based solvents, and ester-based solvents. The water-soluble organic solvent contained as the dispersion medium may be one type or two or more types. The content of water relative to the total mass of the aqueous dispersion medium is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more, and may be 100% by mass.

[0046] It is preferable to add a known catalyst and oxidizing agent to the reaction solution to promote chemical oxidation of the monomer. Examples of the catalyst include transition metal compounds such as ferric chloride, ferric sulfate, ferric nitrate, and cupric chloride. Examples of the oxidizing agent include persulfates such as ammonium persulfate, sodium persulfate, and potassium persulfate.

[0047] The amount of the catalyst to be mixed relative to the total mass of the reaction liquid (including the catalyst) is, for example, preferably from 0.01% by mass to 0.50% by mass, and more preferably from 0.01% by mass to 0.30% by mass.

[0048] The amount of the oxidizing agent relative to the total mass of the reaction liquid (including the oxidizing agent) is, for example, preferably from 0.10% by mass to 1.20% by mass, more preferably from 0.50% by mass to 1.10% by mass, and even more preferably from 0.70% by mass to 1.00% by mass.

[0049] The amount of the monomer to be mixed relative to the total mass of the reaction liquid is, for example, preferably from 0.01% by mass to 2.0% by mass, more preferably from 0.1% by mass to 1.0% by mass, and even more preferably from 0.3% by mass to 0.5% by mass. The amount of the polyanion relative to the total mass of the reaction solution is, for example, preferably 0.1% by mass to 3.0% by mass, more preferably 0.5% by mass to 2.0% by mass, and even more preferably 1.0% by mass to 1.5% by mass. By setting the content within the above preferred range, a conductive polymer dispersion having the conductive complex concentration in the above preferred content can be easily obtained.

[0050] From the viewpoint of making the content ratio of the π-conjugated conductive polymer and the polyanion in the conductive composite formed by the polymerization reaction to be the above-mentioned suitable ratio, the content ratio of the monomer and the polyanion blended in the reaction solution is preferably in the range of 1 part by mass or more and 1,000 parts by mass or less, more preferably 10 parts by mass or more and 700 parts by mass or less, and even more preferably 100 parts by mass or more and 500 parts by mass or less, relative to 100 parts by mass of the monomer.

[0051] The mass ratio of the amount H1 of the polyanion to the amount H2 of the AP to be added to the reaction solution, expressed as H1 / H2, is preferably 0.1 to 3.0, more preferably 0.1 to 0.7, even more preferably 0.1 to 0.6, particularly preferably 0.1 to 0.5, and most preferably 0.1 to 0.4. In the most preferred range, it may be any of 0.1 to 0.3, 0.1 to 0.2, 0.2 to 0.4, and 0.3 to 0.4. When the content is within the above range, the viscosity of the resulting conductive polymer dispersion is reduced, and when a capacitor is produced using this conductive polymer dispersion, the ESR can be reduced while maintaining the capacitance.

[0052] The mass ratio of the amount H3 of the monomer forming the π-conjugated conductive polymer to be added to the reaction solution to the amount H2 of the AP, expressed as H3 / H2, is preferably 0.1 to 1.0, more preferably 0.1 to 0.7, even more preferably 0.1 to 0.6, particularly preferably 0.1 to 0.5, and most preferably 0.1 to 0.4. In the most preferred range, it is preferably 0.1 to 0.4, more preferably 0.1 to 0.3, and even more preferably 0.1 to 0.2. When the content is within the above range, the viscosity of the resulting conductive polymer dispersion is reduced, and when a capacitor is produced using this conductive polymer dispersion, the ESR can be reduced while maintaining the capacitance.

[0053] The reaction temperature in the reaction solution can be, for example, 20 to 30° C. At the reaction temperature, the polymerization reaction is usually completed within about 4 to 12 hours. The completion of the polymerization reaction can be determined by measuring the amount of unreacted monomer in the reaction solution by gas chromatography or the like.

[0054] The catalyst and oxidizing agent added to the reaction liquid are preferably removed from the conductive polymer dispersion after the chemical oxidative polymerization of the monomer. Examples of the removal method include a method of contacting the conductive polymer dispersion with an ion exchange resin to adsorb the catalyst and oxidizing agent to the ion exchange resin, and a method of ultrafiltrating the conductive polymer dispersion to replace the dispersion medium and remove the catalyst and oxidizing agent. Among these, the method using an ion exchange resin is preferable because it is simple. It is preferable to use a cation exchange resin and an anion exchange resin in combination as the ion exchange resin.

[0055] The conductive polymer dispersion thus obtained contains the desired conductive complex. If the catalyst and oxidizing agent are removed from the reaction solution, the solution can be used as is for the production of a capacitor, which will be described later. However, the dispersion medium may be replaced with a desired one, the content concentration of the conductive complex may be adjusted, or a basic compound, a polyol compound, any additive, or the like may be added.

[0056] <<Method of manufacturing a capacitor>> A third aspect of the present invention is a method for producing a capacitor, comprising the steps of applying a conductive polymer dispersion onto a surface of a dielectric layer formed on a surface of an anode made of a porous valve metal body, and drying the applied conductive polymer dispersion to form a solid electrolyte layer. The conductive polymer dispersion contains a conductive complex containing a π-conjugated conductive polymer, a polyanion, and an alkylphosphonic acid having 4 to 12 carbon atoms, and an aqueous dispersion medium for dispersing the conductive complex. The conductive polymer dispersion is preferably the conductive polymer dispersion of the first embodiment.

[0057] The method for manufacturing a capacitor of this embodiment preferably includes a step of oxidizing the surface of an anode made of a porous valve metal to form a dielectric layer (dielectric forming step), a step of arranging a cathode in a position facing the dielectric layer (cathode forming step), and a step of forming a solid electrolyte layer on at least a part of the surface of the dielectric layer (film forming step). Each step will be described below with reference to FIG.

[0058] [Dielectric formation process] In this step, the surface of anode 11 made of a porous valve metal is oxidized to form dielectric layer 12. The method for forming dielectric layer 12 is not particularly limited, and examples thereof include a method in which the surface of anode 11 is anodized in an electrolyte for chemical conversion treatment, such as an aqueous solution of ammonium adipate, an aqueous solution of ammonium borate, or an aqueous solution of ammonium phosphate.

[0059] [Cathode formation process] In this step, the cathode 13 is disposed at a position facing the dielectric layer 12. The method for disposing the cathode 13 is not particularly limited, and examples thereof include a method of forming the cathode 13 using a conductive paste such as a carbon paste or a silver paste, and a method of disposing a metal foil such as an aluminum foil facing the dielectric layer 12.

[0060] [Film forming process] In this step, the conductive polymer dispersion liquid described above is applied to at least a portion of the surface of the dielectric layer 12, and then dried to form the solid electrolyte layer 14.

[0061] Examples of the conductive polymer dispersion coating method include immersion (dip coating), comma coating, reverse coating, lip coating, and microgravure coating. Of these, a method of immersing the anode 11 in the conductive polymer dispersion under reduced pressure is preferred. The immersion method allows the conductive polymer dispersion to be sufficiently applied even to the inside of the porous structure on the surface of the dielectric layer 12. After immersion, the anode is removed and subjected to the next drying process.

[0062] Examples of the drying method include room temperature drying, hot air drying, far infrared drying, etc. Among these, hot air drying is preferred. The drying temperature is, for example, preferably 100 to 180° C., and more preferably 120 to 150° C. The drying time is, for example, preferably 0.2 to 1 hour. After drying, the capacitor can be assembled in the usual manner.

[0063] <Capacitor> A fourth aspect of the present invention is a capacitor comprising an anode made of a porous body of a valve metal, a dielectric layer made of an oxide of the valve metal, a cathode made of a conductive material provided on the dielectric layer opposite to the anode, and a solid electrolyte layer formed between the dielectric layer and the cathode, wherein the solid electrolyte layer contains a conductive complex including a π-conjugated conductive polymer, a polyanion, and an alkylphosphonic acid having 4 to 12 carbon atoms. The solid electrolyte layer is preferably a cured product of the conductive polymer dispersion of the first embodiment. The capacitor of the fourth embodiment can be manufactured by the manufacturing method of the third embodiment.

[0064] An example of an embodiment of the fourth aspect will be described with reference to Fig. 1. A capacitor 10 shown in Fig. 1 includes an anode 11 made of a porous body of a valve metal, a dielectric layer 12 made of an oxide of the valve metal, a solid electrolyte layer 14 formed on the surface of the dielectric layer 12, and a cathode 13 provided on the outermost side. The cathode 13 is provided on the opposite side to the anode 11, with the dielectric layer 12 and the solid electrolyte layer 14 sandwiched therebetween.

[0065] Examples of valve metals constituting the anode 11 include aluminum, tantalum, niobium, titanium, hafnium, zirconium, zinc, tungsten, bismuth, and antimony. Among these, aluminum, tantalum, and niobium are preferable. Specific examples of the anode 11 include an aluminum foil that has been etched to increase its surface area and then oxidized, and a tantalum or niobium particle sintered body that has been oxidized and pelletized. Such a processed body is a porous body with irregularities on the surface.

[0066] The dielectric layer 12 in this embodiment is a layer formed by oxidizing the surface of the anode 11, for example, by anodizing the surface of the metallic anode 11 in an electrolyte such as an aqueous solution of ammonium adipate. Similar to the anode 11, the dielectric layer 12 also has projections and recesses.

[0067] The cathode 13 in this embodiment may be a conductive layer formed from a conductive paste or a metal layer made of a conductive material such as aluminum foil.

[0068] The solid electrolyte layer 14 in this embodiment is formed on the surface of the dielectric layer 12. The solid electrolyte layer 14 covers at least a portion of the surface of the dielectric layer 12, and may cover the entire surface of the dielectric layer 12. The thickness of the solid electrolyte layer 14 may be constant or may not be constant, and may be, for example, between 1 μm and 100 μm.

[0069] <Conductive composite> The conductive complex contained in the solid electrolyte layer contains at least a π-conjugated conductive polymer and a polyanion. The polyanion in the conductive complex is doped into the π-conjugated conductive polymer. The conductive complex preferably contains AP.

[0070] The total content of the π-conjugated conductive polymer, polyanion and AP relative to the total mass of the solid electrolyte layer is preferably 1% by mass to 99% by mass, more preferably 50% by mass to 98% by mass, and even more preferably 70% by mass to 97% by mass. The above range is preferable because it makes it easier to reduce the equivalent series resistance of the capacitor.

[0071] <Alkylphosphonic acid> The solid electrolyte layer contains alkylphosphonic acid (AP) with 4 to 12 carbon atoms, which reduces the ESR of the capacitor.

[0072] The mass ratio of the polyanion content G1' to the AP content G2' contained in the solid electrolyte layer, expressed as G1' / G2', is preferably 0.1 to 3.0, more preferably 0.1 to 0.7, even more preferably 0.1 to 0.6, particularly preferably 0.1 to 0.5, and most preferably 0.1 to 0.4. In the most preferred range, it may be any of 0.1 to 0.3, 0.1 to 0.2, 0.2 to 0.4, and 0.3 to 0.4. Within the above range, the ESR can be reduced while maintaining the capacitance of the capacitor.

[0073] The mass ratio of the content G3' of the π-conjugated conductive polymer contained in the solid electrolyte layer to the content G2' of the AP, expressed as G3' / G2', is preferably 0.1 to 1.0, more preferably 0.1 to 0.7, even more preferably 0.1 to 0.6, particularly preferably 0.1 to 0.5, and most preferably 0.1 to 0.4. In the most preferred range, it is preferably 0.1 to 0.4, more preferably 0.1 to 0.3, and even more preferably 0.1 to 0.2. Within the above range, the ESR can be reduced while maintaining the capacitance of the capacitor.

[0074] <Basic compounds> The solid electrolyte layer may further contain one or more of the above-mentioned basic compounds. By containing a basic compound, the ESR of the capacitor can be further reduced.

[0075] The content ratio of the basic compound in the solid electrolyte layer is, for example, preferably 1 part by mass or more and 1,000 parts by mass or less, more preferably 5 parts by mass or more and 100 parts by mass or less, and even more preferably 10 parts by mass or more and 50 parts by mass or less, relative to 100 parts by mass in total of the π-conjugated conductive polymer and the polyanion. Within the above preferred range, the ESR of the capacitor can be further reduced.

[0076] <Polyol compound> The solid electrolyte layer may further contain one or more of the above-mentioned polyols. By containing a polyol, the ESR of the capacitor can be further reduced.

[0077] The total content of the polyol compounds contained in the solid electrolyte layer is, for example, preferably 100 parts by mass or more and 10,000 parts by mass or less, more preferably 200 parts by mass or more and 2,000 parts by mass or less, and even more preferably 300 parts by mass or more and 1,000 parts by mass or less, relative to 100 parts by mass in total of the π-conjugated conductive polymer and polyanion contained in the solid electrolyte layer. Within the above preferred range, the ESR of the capacitor can be further reduced.

[0078] [Electrolyte] The capacitor of this embodiment may have an electrolyte that impregnates the solid electrolyte layer. Examples of the solvent constituting the electrolytic solution include alcohol-based solvents such as ethylene glycol, diethylene glycol, propylene glycol, 1,4-butanediol, and glycerin; lactone-based solvents such as γ-butyrolactone, γ-valerolactone, and δ-valerolactone; sulfur-based solvents such as sulfolane, dimethyl sulfoxide, and dimethyl sulfone; amide-based solvents such as N-methylformamide, N,N-dimethylformamide, N-methylacetamide, and N-methylpyrrolidinone; nitrile-based solvents such as acetonitrile and 3-methoxypropionitrile; and water. Examples of the electrolyte constituting the electrolytic solution include organic acids such as adipic acid, glutaric acid, succinic acid, benzoic acid, isophthalic acid, phthalic acid, terephthalic acid, maleic acid, toluic acid, enanthic acid, malonic acid, formic acid, decanedicarboxylic acids such as 1,6-decanedicarboxylic acid and 5,6-decanedicarboxylic acid, octanedicarboxylic acids such as 1,7-octanedicarboxylic acid, azelaic acid, and sebacic acid; or boric acid, a polyhydric alcohol complex compound of boric acid obtained from boric acid and a polyhydric alcohol; inorganic acids such as phosphoric acid, carbonic acid, and silicic acid as anion components, and primary amines (methylamine, ethylamine, propylamine, butylamine, ethylenediamine, etc.), secondary amines (dimethylamine, diethylamine, dipropylamine, methylethylamine, diphenylamine, etc.), tertiary amines (trimethylamine, triethylamine, tripropylamine, triphenylamine, 1,8-diazabicyclo(5,4,0)-undecene-7, etc.), tetraalkylammonium (tetramethylammonium, tetraethylammonium, tetrapropylammonium, tetrabutylammonium, methyltriethylammonium, dimethyldiethylammonium, etc.), etc., as a cationic component.

[0079] The capacitor of this embodiment is not limited to the above configuration, and a separator may be provided between the dielectric layer and the cathode. An example of a capacitor having a separator provided between the dielectric layer and the cathode is a wound capacitor. Examples of the separator include sheets (including nonwoven fabrics) made of cellulose, polyvinyl alcohol, polyester, polyethylene, polystyrene, polypropylene, polyimide, polyamide, polyvinylidene fluoride, etc., and nonwoven fabrics of glass fibers. The density of the separator is, for example, 0.1 g / cm 3 More than 1.0g / cm 3 The following are included: When a separator is provided, a method of forming a cathode by impregnating the separator with carbon paste or silver paste can also be applied. EXAMPLES

[0080] (Production Example 1) Production of polystyrene sulfonic acid 1 206 g of sodium styrenesulfonate was dissolved in 1000 ml of ion-exchanged water, and while stirring at 80° C., 1.14 g of an oxidizing agent solution of ammonium persulfate previously dissolved in 10 ml of water was added dropwise over 20 minutes, and the solution was stirred for 12 hours. 1000ml of sulfuric acid diluted to 10% by mass was added to the obtained sodium polystyrene sulfonate solution, and about 1000ml of the solvent from the obtained polystyrene sulfonic acid solution was removed by ultrafiltration. Next, 2000ml of ion-exchanged water was added to the remaining liquid, and about 2000ml of the solvent was removed by ultrafiltration to wash the polystyrene sulfonic acid with water. This washing operation was repeated three times. Water in the obtained solution was removed under reduced pressure to obtain colorless solid polystyrene sulfonic acid (PSS). 10 g of this polystyrene sulfonic acid was dissolved in 90 g of ion-exchanged water to obtain a 10% by mass aqueous solution of polystyrene sulfonic acid.

[0081] The weight average molecular weight (Mw) of the polystyrene sulfonic acid aqueous solution obtained above was measured by gel permeation chromatography (GPC) using pullulan of known weight average molecular weight as the standard substance, and the weight average molecular weight was found to be 200,000.

[0082] The weight-average molecular weight was measured using a Prominence high-performance liquid chromatograph manufactured by Shimadzu Corporation, 0.1% NaNO3 aqueous solution as the solvent, a Shodex OHpack SB-806M HQ column, and a RID-20A detector, with the solvent temperature set to 40°C, the flow rate set to 0.6 ml / min, the PSS concentration in the sample set to 0.1 mass%, 100 μl of the sample filtered through a membrane filter with a pore size of 0.2 μm was injected, and the analysis software Lab Solutions (manufactured by Shimadzu Corporation) was used.

[0083] (Production Example 2) Production of polystyrene sulfonic acid 2 206 g of sodium styrenesulfonate was dissolved in 1000 ml of ion-exchanged water, and while stirring at 80° C., 0.38 g of an oxidizing agent solution of ammonium persulfate previously dissolved in 10 ml of water was added dropwise over 20 minutes, and the solution was stirred for 12 hours. 1000ml of sulfuric acid diluted to 10% by mass was added to the obtained sodium polystyrene sulfonate solution, and about 1000ml of the solvent from the obtained polystyrene sulfonic acid solution was removed by ultrafiltration. Next, 2000ml of ion-exchanged water was added to the remaining liquid, and about 2000ml of the solvent was removed by ultrafiltration to wash the polystyrene sulfonic acid with water. This washing operation was repeated three times. Water in the resulting solution was removed under reduced pressure to obtain colorless solid polystyrene sulfonic acid. Next, 10 g of the obtained polystyrene sulfonic acid was dissolved in 90 g of ion-exchanged water to obtain a 10% by mass aqueous polystyrene sulfonic acid solution. The weight average molecular weight of the polystyrene sulfonic acid (PSS) obtained above, measured by GPC in the same manner as in Production Example 1, was 540,000.

[0084] (Production Example 3) Preparation of Capacitor Element After connecting an anode lead terminal to the etched aluminum foil (anode foil), a voltage of 40 V was applied in a 10% by mass aqueous solution of ammonium adipate to perform chemical conversion (oxidation treatment) and form dielectric layers on both sides of the aluminum foil to obtain an anode foil. Next, opposing aluminum cathode foils to which cathode lead terminals were welded were laminated on both sides of the anode foil via a cellulose separator, and the resultant was rolled up into a cylindrical shape to obtain a capacitor element.

[0085] Example 1: Preparation of conductive polymer dispersion 3.0 g of 3,4-ethylenedioxythiophene (EDOT), 90 g of the polystyrene sulfonic acid (10 mass % aqueous solution) of Production Example 1, 4.5 g of n-hexylphosphonic acid, and 325 g of ion-exchanged water were mixed at 20°C. The resulting mixed solution was kept at 20° C., and 0.3 g of ferric sulfate was added while stirring. Next, a solution of 6.6 g of sodium persulfate dissolved in 293.4 g of ion-exchanged water was slowly added, and the resulting reaction solution was reacted with stirring for 8 hours. By the above reaction, a conductive polymer dispersion was obtained containing a conductive complex (PEDOT-PSS-AP) containing poly(3,4-ethylenedioxythiophene), which is a π-conjugated conductive polymer, polystyrene sulfonic acid, and n-hexylphosphonic acid, and water, which is a dispersion medium.

[0086] When the obtained conductive polymer dispersion was analyzed by GPC, the amount of unpolymerized EDOT was below the detection limit.

[0087] To this conductive polymer dispersion, 78 g of Duolite C255LFH (a cation exchange resin, manufactured by Sumika Chemtex Corporation) and 78 g of Duolite A368S (anion exchange resin, manufactured by Sumika Chemtex Corporation) were added, and the ion exchange resin was removed by filtration to obtain 710 g of a conductive polymer dispersion from which the oxidant and the catalyst had been removed, and the solid content (non-volatile components) was measured. Next, water was distilled off under reduced pressure from the obtained conductive polymer dispersion using an evaporator to make the solid content 1.6 mass %. Imidazole was added to 100 g of the obtained conductive polymer dispersion to adjust the pH to 2.5, and 8 g of diethylene glycol was added.

[0088] The capacitor element obtained in Production Example 3 was immersed in the above conductive polymer dispersion liquid under reduced pressure and then dried for 30 minutes in a hot air dryer at 125°C to form a solid electrolyte layer containing a conductive complex on the surface of the dielectric layer. Next, the capacitor element having the above-mentioned solid electrolyte layer formed thereon was loaded into an aluminum case, and the case was sealed with a sealing rubber to prepare a capacitor.

[0089] Example 2 A capacitor was produced in the same manner as in Example 1, except that the amount of n-hexylphosphonic acid was changed to 9 g.

[0090] Example 3 A capacitor was produced in the same manner as in Example 1, except that the amount of n-hexylphosphonic acid was changed to 13.5 g.

[0091] Example 4 A capacitor was produced in the same manner as in Example 1, except that the amount of n-hexylphosphonic acid was changed to 18.0 g.

[0092] Example 5 A capacitor was produced in the same manner as in Example 1, except that the amount of n-hexylphosphonic acid was changed to 22.5 g.

[0093] Example 6 A capacitor was produced in the same manner as in Example 4, except that n-butylphosphonic acid was used instead of n-hexylphosphonic acid.

[0094] Example 7 A capacitor was produced in the same manner as in Example 4, except that n-octylphosphonic acid was used instead of n-hexylphosphonic acid.

[0095] Example 8 A capacitor was produced in the same manner as in Example 4, except that n-hexylphosphonic acid was replaced with n-decylphosphonic acid.

[0096] Example 9 A capacitor was produced in the same manner as in Example 4, except that n-dodecylphosphonic acid was used instead of n-hexylphosphonic acid.

[0097] Example 10 A capacitor was produced in the same manner as in Example 4, except that the amount of polystyrene sulfonic acid (10% aqueous solution) in Production Example 1 was changed from 90 g to 60 g.

[0098] Example 11 A capacitor was produced in the same manner as in Example 4, except that 90 g of polystyrene sulfonic acid (10% aqueous solution, Mw: 200,000) of Production Example 1 was replaced with 90 g of polystyrene sulfonic acid (10% aqueous solution, Mw: 540,000) of Production Example 2.

[0099] Comparative Example 1 A capacitor was produced in the same manner as in Example 1, except that n-hexylphosphonic acid was not added.

[0100] Comparative Example 2 A capacitor was produced in the same manner as in Example 4, except that 18.0 g of n-hexylphosphonic acid was changed to 18.0 g of n-ethylphosphonic acid.

[0101] Comparative Example 3 An investigation was carried out in the same manner as in Example 1 except that polystyrene sulfonic acid was not added. However, particles were precipitated and a conductive polymer dispersion liquid could not be obtained, so the investigation was discontinued.

[0102] Comparative Example 4 An investigation was carried out in the same manner as in Example 4, except that 18.0 g of n-hexylphosphonic acid was changed to 18.0 g of n-octadecylphosphonic acid in Example 4. However, the conductive polymer dispersion foamed violently, and a conductive polymer dispersion suitable for viscosity measurement and capacitor production could not be obtained, so the investigation was discontinued.

[0103] [pH measurement] The pH was measured at 25°C by a conventional method using a commercially available pH meter.

[0104] [Method of measuring viscosity] A conductive polymer dispersion liquid adjusted to a solid content of 1.6% by mass was obtained as described in Example 1, and this was dispersed using a high-pressure homogenizer. A tuning fork vibration viscometer (model number: SV-10, manufactured by A&D Corporation) was used as a sample to measure viscosity at 25°C in accordance with JIS Z8803:2011 (method of measuring viscosity using a vibration viscometer). 1 Pa s (pascal second) was calculated as 1000 cP (centipoise).

[0105] <Evaluation> [Capacitance / Equivalent Series Resistance] For each capacitor, the capacitance (unit: μF) at 120 Hz and the equivalent series resistance (ESR) (unit: mΩ) at 100 kHz were measured using an LCR meter ZM2376 (manufactured by NF Corporation). The measurement results are shown in Table 1.

[0106] [Table 1]

[0107] <Result> The conductive polymer dispersion of the examples contained alkylphosphonic acid (AP) having 4 to 12 carbon atoms along with a π-conjugated conductive polymer and a polyanion as a conductive complex, and therefore had a reduced viscosity. Compared with Comparative Example 1 in which no AP was blended, and Comparative Example 2 in which the AP had an insufficient carbon number, the viscosity of the conductive polymer dispersion blended with a specific AP of the examples was significantly reduced, and therefore it is understood that the PEDOT-PSS complex of the examples contains AP. AP has a phosphonic acid group (-P(=O)(-OH)2), and is therefore considered to be doped into PEDOT in the same way as PSS. In addition, in the capacitors produced using the conductive polymer dispersions of the examples, it was possible to reduce the ESR while maintaining the capacitance. The greater the amount of AP contained in the conductive polymer dispersion, the lower the viscosity and the lower the ESR of the capacitor.

[0108] On the other hand, the conductive polymer dispersion of Comparative Example 1 did not contain AP, so the viscosity was high and the ESR of the capacitor was poor. The conductive polymer dispersion of Comparative Example 2 contained an alkylphosphonic acid having 2 carbon atoms, but the viscosity was high and the ESR of the capacitor was poor. In Comparative Example 3, no polyanion was blended, so a conductive composite dispersible in an aqueous dispersion was not obtained, and a capacitor could not be manufactured. The conductive polymer dispersion of Comparative Example 4 contained an alkylphosphonic acid having 18 carbon atoms, but foamed violently, making it difficult to manufacture a capacitor. From these results, it is understood that in each Example, an alkylphosphonic acid having 4 to 12 carbon atoms is contained in the conductive complex, and forms PEDOT-PSS-AP, which is stably dispersed in the aqueous solvent. [Explanation of symbols]

[0109] 10 Capacitor 11 Anode 12 Dielectric layer 13 Cathode 14 Solid electrolyte layer

Claims

1. A conductive polymer dispersion liquid containing a π-conjugated conductive polymer, an alkylphosphonic acid having 4 to 12 carbon atoms, a polyanion, and an aqueous dispersion medium.

2. The conductive polymer dispersion according to claim 1 , wherein the content of water relative to the total mass of the aqueous dispersion medium is 70 mass % or more.

3. The π-conjugated conductive polymer is poly(3,4-ethylenedioxythiophene), or the polyanion is polystyrenesulfonic acid, or 3. The conductive polymer dispersion according to claim 2, wherein the π-conjugated conductive polymer is poly(3,4-ethylenedioxythiophene) and the polyanion is polystyrenesulfonic acid.

4. A monomer for forming a π-conjugated conductive polymer is polymerized in a reaction solution containing a polyanion, an alkylphosphonic acid having 4 to 12 carbon atoms, and an aqueous dispersion medium, A method for producing a conductive polymer dispersion, comprising a polymerization step of forming a conductive complex containing the π-conjugated conductive polymer, the polyanion, and an alkylphosphonic acid having 4 to 12 carbon atoms.

5. The present invention relates to a valve metal porous body, and a cathode made of a conductive material and provided on the dielectric layer opposite to the anode. The solid electrolyte layer comprises a conductive complex containing a π-conjugated conductive polymer, a polyanion, and an alkylphosphonic acid having 4 to 12 carbon atoms.

6. The capacitor according to claim 5 , wherein the solid electrolyte layer further contains a basic compound.

7. The capacitor of claim 6 , wherein the basic compound is a nitrogen-containing aromatic compound.

8. The capacitor according to claim 7 , wherein the solid electrolyte layer further contains a polyol compound containing two or more hydroxyl groups.

9. The capacitor of claim 8 , wherein the polyol compound is diethylene glycol.

10. 1. A method for manufacturing a capacitor, comprising the steps of: applying a conductive polymer dispersion onto a surface of a dielectric layer formed on a surface of an anode made of a porous valve metal; and drying the applied conductive polymer dispersion to form a solid electrolyte layer, The conductive polymer dispersion liquid comprises a conductive complex containing a π-conjugated conductive polymer and a polyanion, and an alkylphosphonic acid having 4 to 12 carbon atoms, and an aqueous dispersion medium for dispersing the conductive complex.

Citation Information

Patent Citations

  • Method of manufacturing organic solar cell

    JP2007095782A

  • Conductive membrane, conductive polymer composition, conductive polymer material, and device

    JP2010047671A

  • Electroconductive polymer membrane and device using the same

    JP2010174163A

  • Capacitor and method for producing the same, and conductive polymer dispersion

    JP2020100744A

  • Manufacturing method of positive electrode for capacitor, and manufacturing method of capacitor

    JP2021190654A